Efektivitas Penerapan Sistem Merit Berbasis Digital Dalam Manajemen Aparatur Sipil Negara Di Provinsi Kepulauan Riau - Firman, Firman; Sholeh, Chaereyranba; Supriyadi, Hafiz; Karniya, Hanthyta Dwi (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
This study aims to determine the effectiveness of System Merit in State Civil Apparatus Management in Riau Islands Province to increase apparatus productivity in quantity and quality. The study uses descriptive research methods with a qualitative approach. The result of this research is that there needs to be a high spirit of work to provide excellent service by applying a merit system. Development is required in the form of evaluation of institutional structuring, assessment of performance achievement, employee attendance discipline, and strategy and program Implementation of the Regional Merit System in Riau Islands Province. This research recommends that implementing a merit system in A.S.N. management in Riau Islands Province can improve A.S.N. competence and as strong leverage in performance improvement and transformation of government organizations with simplification of bureaucracy, work models, organizational culture, and strategic values developed.